2017
DOI: 10.1016/j.triboint.2017.06.031
|View full text |Cite
|
Sign up to set email alerts
|

History effect on squeal with a mesoscopic approach to friction materials

Abstract: Friction pads are made by a recipe of numerous components leading to a heterogeneous material. The originality of this paper is firstly to propose a method leading to identify local mechanical properties of friction a pad, performed at different locations, via an indentation test. Secondly, the mechanical properties obtained for each location are introduced in a modeling to perform a complex modal analysis. A comparison with an equivalent homogeneous friction pad is performed to highlight the difference. Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Dai et al [15] carried out a numerical investigation of the effect of adding chamfers to pad linings and found that chamfering lowers the propensity for instability. More recent works introduce enriched material and surface parameters and their evolution with loading, showing as in experiments, that they could influence the instability [16]. Reference [17] propose a numerical strategy which allows to integrate the roughness at the interface into a complete brake with a squeal study.…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al [15] carried out a numerical investigation of the effect of adding chamfers to pad linings and found that chamfering lowers the propensity for instability. More recent works introduce enriched material and surface parameters and their evolution with loading, showing as in experiments, that they could influence the instability [16]. Reference [17] propose a numerical strategy which allows to integrate the roughness at the interface into a complete brake with a squeal study.…”
Section: Introductionmentioning
confidence: 99%
“…In the brake industry, the different noise emissions, resulting from the contact between the lining material and the disc surface during the braking phase, are associated to these different frictional scenarios. In fact, while high frequency squeal noise is more likely to be associated to mode coupling instabilities [24][25][26][27][28], groan noise is more likely to be associated to stick-slip instabilities [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…From an experimental point of view, both industrial and academic test rigs have been developed in order to propose contributions for a better understanding of the phenomena of brake squeal, as well as to investigate which physical phenomena could be the cause of the brake noise. For example some rely on research more focused on friction-induced vibrations [6,7,8,9,10,11,12,13,14,15,16,17], while others study the subject via thermal considerations [18,19] or a tribological point of view [20,21,22,23,24,25]. On the other hand, some researchers [23,26,27,28] are also interested in dealing with the problem of brake squeal by considering additionally the problem of acoustic radiated noise due to friction-induced vibration or roughness at the frictional interface.…”
Section: Introductionmentioning
confidence: 99%